Attitude of Students and Audiologist Professionals towards Patient-Centered Care in Audiology - Goyal, Swati; E., Prajwal Kumar; Murthy, Chethana P.; Prabhu, Prashanth P. (Journal of Health and Allied Sciences NU, 2024)
Background In audiology, the service model has always been practitioner-centric or techno-centric. However, the model has evolved into client-centric over the years. Patient centeredness is a growing trend in healthcare as it improves the outcomes of the intervention and patient satisfaction. This study was conducted with the aim of determining the preferences of undergraduates, postgraduates, and working professionals toward a patient-centered framework for the service delivery model.Materials & methods This study employed a survey design where the data was collected using an online questionnaire (patient–practitioner orientation scale). A total of 60 individuals participated in the survey which included undergraduate students, postgraduate students, and working professionals.Results The analysis of the findings revealed that there was no significant difference in the attitude toward preferences between postgraduate students and working professionals. However, a significant difference was found between undergraduate students and working professionals and undergraduate students and postgraduate students.Conclusion This study concludes that the postgraduate students and working professionals are more patient-centric than the undergraduate students. However, further studies are needed to compare the attitudes of working professionals with varying years of work experience.
Keywords: service delivery model; audiologist's attitude; audiological rehabilitation & patient practitioner orientation scale (PPOS)